The Effect of Moving Target Drills on Futsal Passing Accuracy at SMPN 5 Seluma - Rahmad Trigono; Feby Elra Perdima; Mariska Febrianti (Educative Sportive, 2026)
This study was motivated by the low passing accuracy of the futsal students in the extracurricular program at SMP Negeri 5 Seluma, as evidenced by the lack of precision in pass direction, inappropriate kicking power, and poor ability to pass in dynamic game situations. These conditions are believed to be influenced by training methods that remain conventional and do not adequately simulate actual match conditions. This study aims to determine the effect of moving target training on the futsal passing accuracy of extracurricular students at SMP Negeri 5 Seluma. This study used a quantitative method with an experimental approach and a one-group pretest-posttest design. The study sample consisted of 20 students selected using total sampling. Data collection was conducted through passing accuracy tests before and after the intervention, then analyzed using normality tests, homogeneity tests, and a paired sample t-test with the assistance of SPSS software. The results of the study show that the students’ average passing accuracy score increased from 5.20 on the pre-test to 6.70 on the post-test. The hypothesis test yielded a significance value of 0.000 < 0.05, so Ha was accepted and H0 was rejected. These findings indicate that moving target drills have a significant effect on improving the passing accuracy of students in the futsal extracurricular program at SMP Negeri 5 Seluma. Thus, moving target drills can be used as an effective alternative training method to improve passing skills in futsal.